Factors Affecting The Adoption of Banana Crop Insurance among Banana Farmers in Chitwan District, Nepal - Pant, Priyanka; Singh, Om Prakash; Kapri, Rajani; Sapkota, Smriti; Bhatta, Sushmita; Mishra, Binayak Prakash (Nepalese Journal of Agricultural Sciences, 2026)
An investigation was carried out in Chitwan district of Nepal in 2021 to identify the factors affecting the adoption of banana crop insurance among banana farmers. Employing multistage purposive random sampling, 80 banana farm households were selected. Primary data were gathered through semi-structured questionnaires administered to the household head. The analysis was carried out using a binary pro bit model. Results revealed that the annual income of the household significantly and positively affected the adoption of banana insurance. In the present context, farm households with higher annual incomes should be targeted for the efficient adoption of insurance. Thus, it is necessary to improve the income of farmers through multiple approaches such as trainings related to agribusiness management, proper access to cost-effective input market and prices, establishment of efficient marketing channels and value addition for the better adoption. Agricultural cooperatives and farmers groups should be further strengthened to promote collective agribusiness. Subsidy on the crop insurance should be further raised and export opportunities should be explored